Alienation and Fragmentation; A Modern Critical Analysis of Zulfikar Ghose's Poem “Disturbed Nights”: https://doi.org/10.5281/zenodo.16894228 - Izaz Ali; Shumaila Fayaz (`, 2025)
This research study delves into the mental crisis of modern humans as they face alienation and fragmentation of psyche related to the industrial revolution and materialistic pursuits in their lives. This paper aims to provide a deep analysis of modern humans and their sufferings due to modern age technological developments through the poem, “Disturbed Nights” written by Zulfikar Ghose. Ghose in his poem tries to awake the anxious minds of modern men who are no more than puppets to the machines of the said age. Though, multitude of writings are out there that focus on the mental crisis and dilemma of modern world, but hardly any body of work can be found that demonstrates the diasporic consciousness and the multidimensional richness of South Asian poetry in general and Zulfikar Ghose in specific, as a blend of the effects of both modernism and colonialism on human’s mentality. Therefore, this poem is a masterpiece that mirrors the chaos and troubles of the modern age as well as the struggles of post-colonial humans dealing with the resulting alienation and fragmentation. This research tries to fill the gap by alluding to the sufferings of the diasporic community who experienced the traumas of colonialism and its aftermath in the form of alienation, fragmentation, isolation, disconnection, and mental crisis. Keywords: Mental Crisis, Modern Humans, Alienation, Fragmentation, Diaspora, Disturbed Nights by Zulfikar Ghose.